Impact of Service Quality of e-banking on Customer Satisfaction: A Study of Panchapuri Municipality - Bhandari, Nirajan (Journal of Gurubaba, 2025)
This study Impact of Service Quality of e-banking on Customer Satisfaction: A Study of Panchapuri Municipality. Since customer satisfaction is a high priority as one of the goals of banks, this study aims to investigate the effect of e-banking service quality on customer satisfaction. The survey includes respondents of residents from Panchapuri Municipality households, student, government employment etc. The study used a descriptive research design where data was collected from 200 respondents who were willing to participate using a structured questionnaire. The majority of the respondent are female, and youths. This study has further tried to examine the relationship between these influencing factors and customer satisfaction. This study is reliability, security and responsiveness has a significant positive effect on customer satisfaction whereas efficiency has insignificant effect on customer satisfaction. The respondents argue with the reliable service, security maintained and timely response of bank. The correlations between responsive and customer satisfaction, reliability responsiveness were found most significant. Bank should think in making their e banking service more efficient so that customer get multiple service in a single click.